Evaluation of the Efficiency of the Sample Inactivation Reagent in the Abbott RealTime MTB Assay for Inactivation of Mycobacterium tuberculosis - Qi, Chao (J Clin Microbiol, 2015)
The Abbott RealTime MTB assay is a nucleic acid amplification test (NAAT) for the detection of Mycobacterium tuberculosis complex DNA. The sample inactivation procedure used in the assay, consisting of one part sample treated with 3 parts inactivation reagent for 60 min, effectively reduced viscosity and inactivated M. tuberculosis in clinical specimens.